2022
DOI: 10.1038/s41598-022-18045-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between just world belief and wellbeing, cheating behaviors, and academic work behaviors during COVID 19 among university students

Abstract: Is the belief in a just world among students also stable under COVID-19? To answer this question, a study was conducted with university students from Germany (n = 291). The aim of the study was to analyze the predictive performance of the personal belief in a just world (PBJW) on students' life satisfaction and academic cheating and to take into account important mediators from the university context such as fellow student justice, lecturer justice, and procrastination. Derived from existing research, universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 121 publications
1
9
0
Order By: Relevance
“…In accordance with this, previous researchers have stated that if students perceive injustice, they will typically respond with anger and disappointment and may attempt to stand against authority through academic dishonesty (Phutikettrkit and Thomas, 2019;Münscher et al, 2020). Several researchers have recently found a negative influence between lecturers' justice and online cheating (Münscher, 2022;Münscher et al, 2020). It indicated that when lecturers treat students fairly, students will tend to not engage in online cheating.…”
Section: Perceived Lecturer Justice and Online Cheatingmentioning
confidence: 79%
See 4 more Smart Citations
“…In accordance with this, previous researchers have stated that if students perceive injustice, they will typically respond with anger and disappointment and may attempt to stand against authority through academic dishonesty (Phutikettrkit and Thomas, 2019;Münscher et al, 2020). Several researchers have recently found a negative influence between lecturers' justice and online cheating (Münscher, 2022;Münscher et al, 2020). It indicated that when lecturers treat students fairly, students will tend to not engage in online cheating.…”
Section: Perceived Lecturer Justice and Online Cheatingmentioning
confidence: 79%
“…Despite the demonstrated correlation between fairness and cheating, there are still gaps in the prior studies' findings. Some researchers discovered a positive significant correlation between fairness and dishonesty (Kaufmann and Tatum, 2018;Nigjeh et al, 2019;Münscher et al, 2020;Münscher, 2022), whereas other studies demonstrated a weak positive relationship (Akbas lı et al, 2019;Phutikettrkit and Thomas, 2019). Recognizing the disparity, we attempted to bridge the gap by proposing spirituality as a moderating variable.…”
Section: Spirituality and Online Cheatingmentioning
confidence: 99%
See 3 more Smart Citations